The Effect of Company Characteristics and Corporate Governance on the Practices of Intellectual Capital Disclosure - Isnalita; Romadhon, Fitri (International Research Journal of Business Studies, 2018)
This study aimed to reveal the effect of company characteristics, company size i.e., profitability, leverage, liquidity, and industry type; and corporate governance structure, consisting of the audit firm size and the independent commissioners’ composition, on the intellectual capital disclosure. This research applied quantitative approach by testing seven independent variables through multiple linear regression analysis. The samples taken were 80 annual reports from companies listed in the LQ-45 index in the year 2012-2013. The method employed to select the samples was purposive sampling. Content analysis was applied to analyze the intellectual capital disclosure. This study revealed that only the company size showed significant positive impact to the disclosure of intellectual capital, while profitability, leverage, liquidity, industry type, the audit firm size, and the independent commissioners composition did not bring significant effect. In addition, based on the results of content analysis it can be concluded that the intellectual capital disclosure is quite low, amounting to 46.9%, with relational capital amounted to 34.74%, 32.54% of structural capital, and human capital reached 32.71%.